Molecular biology and pathology : a guidebook for quality control (Oxford, United Kingdom : Elsevier Science, 1993)
This is the first handbook to provide an all-in-one guide to establishing molecular biology protocols with requisite quality control. Molecular Biology and Pathology will help professionals sift through the incredible wealth of information available on molecular biology, specifically as it relates to the clinical arena of molecular pathology. This handbook provides excellent training information, and the concern of safety is discussed extensively. The handbook can serve as a primer and reference for those interested in the technical topics described, including the brief discussion of DN.
Front Cover; Molecular Biology and Pathology; Copyright Page; Table of Contents; Contributors; Preface; Acknowledgments; Chapter 1. Establishing a Clinical Molecular Biology Laboratory; Introduction; Clinical Importance; Preliminary Setup of the Laboratory; Necessary Equipment; Molecular Pathology Proficiency Surveys and Standards; Conclusion; Acknowledgments; References; Chapter 2. Safety in the Molecular Biology Laboratory; Hazards; General Safety Considerations; Hazard Communication Program; Acknowledgment; References. Chapter 3. Specimen Procurement, Processing, Tracking, and Testing by the Southern BlotQuality Control; Southern Transfer; DNA Bank; Acknowledgment; References; Chapter 4. Quality Control of the B/T Cell Gene Rearrangement Test; Summary; Introduction; Controls; References; Chapter 5. The BCR/abl Gene Rearrangement in Chronic Myelogenous Leukemia and Acute Leukemias: Clinical Perspectives and Quality Control; Introduction; Molecular Pathology of Chronic Myelogenous Leukemia; Molecular Pathology of Ph-Positive Acute Leukemias. Molecular-Clinical Correlations and Diagnostic Use of the BCR/abl Gene Rearrangement TestsChronic Myelogenous Leukemia; Conclusion; References; Chapter 6. Human Papillomavirus DNA Detection and Typing; Collection, Handling, and Transport; Examining Kit Quality Control; Southern Blot; Dot Blot; In Situ Hybridization; Capture Hybridization; Polymerase Chain Reaction; Parallel Testing; Quality Control Documentation; Summary; References; Chapter 7. Quality Control of the Polymerase Chain Reaction; Polymerase Chain Reaction: The Methodology; Setting Up a Polymerase Chain Reaction Laboratory. Laboratory Techniques and PracticesEnzymatic and Chemical Methods of Amplicon Carry-Over Containment; Optimization of Polymerase Chain Reaction; Quality Control; Summary; References; Chapter 8. The Molecular Pathology of Cystic Fibrosis: A Clinical Laboratory Perspective; Introduction; Population Screening; Family Studies; Individual Carrier Risk Assessment; Methods; Conclusion; References; Chapter 9. Duchenne and Becker Muscular Dystrophy: Current Diagnostics; Clinical Aspects; Genetics; DNA Analysis; References; Chapter 10. Quality Control in DNA Profiling Tests; Introduction. Restriction Fragment Length Polymorphism Test MethodologyConclusion; References; Chapter 11. Incorporating Molecular Pathology into Medical Technology Training Programs; Introduction; Clinical Training; Academic Coursework; Prospectus; Conclusion; References; Suggested Readings; Appendix 1. Procedure Manual for the B/T Cell Gene Rearrangement Test and bar Analysis; Gene Rearrangement in B and T Cells; Recipes for Solutions Prepared in the Laboratory/Glassware Cleaning; Calibration; Quality Control; Sample Collection.
Includes index.
Keywords: PATHOLOGY, MOLECULAR -- QUALITY CONTROL